Coping with religious-based segregation and discrimination: Efforts in an Indonesian context - Iwamony, Rachel (HTS teologiese studies, 2020)
The aim of this article was to describe and analyse religious-based segregation and discrimination in the Moluccas and West Java, two places in Indonesia. Generally, people live peacefully side by side. However, in some places, social conflicts occur. By means of interview and focus group discussion, the researcher observed and concluded that the main cause of the conflicts was religious discrimination. In Moluccas, Christians and Muslims live separately. In coping with that problem, the local leaders keep trying to talk directly with one another and to engage in social acts together. Nevertheless, there are still some indigenous people experiencing religious discrimination. One of them is Sunda Wiwitan. Their access to acquire birth certificates has been hindered. Consequently, they have limited access to public services, including education and healthcare. However, their religious principles encourage them to be compassionate towards others and prohibit them from causing danger to others.Contribution: Religious understanding and reconciliation have become important topics in the midst of religious conflict. This article contributes to promote religious reconciliation through some very simple and practical ways that reflect the core of religious teachings.